CDCA8 expression and its clinical relevance in patients with bladder cancer. Issue 34 (August 2018) - Bi, Yaqiong; Chen, Song; Jiang, Jiazhi; Yao, Jie; Wang, Gang; Zhou, Qiang; Li, Sheng
Abstract : Abstract: Cell division cycle associated 8 (CDCA8) overexpression is detected in various malignant tumors and closely associated with tumor growth. However, the correlations of CDCA8 expression with clinicopathological factors and prognosis of bladder cancer (BC) remain unclear. The purpose of this study was to identify the expression of CDCA8 and its clinical relevance in BC patients. GEO datasets were employed to obtain CDCA8 expression data and its clinical information in BC samples. Real-time PCR (RT-PCR) was performed to detect the expression of CDCA8 in BC and the adjacent normal tissues. Nonpaired t test was used to statistically analyze the difference between the 2 groups. Cox univariable and multivariable analyses of overall survival (OS) and cancer specific survival (CSS) among BC patients were performed. Biological processes or signaling pathways that might mediate the activity of CDCA8 in BC were analyzed. CDCA8 levels were significantly higher in BC (8.870 ± 0.08281 vs 7.472 ± 0.07035, P <  .0001). CDCA8 expression was significantly associated with tumor progression ( P =  .001), T stage ( P <  .0001), N stage ( P =  .013), and grade ( P <  .0001). Higher expression of CDCA8 predicted poor cancer-specific survival ( P  < .0001, HR = 0.2752, 95% CI:0.1364-0.5554) and overall survival ( P  < .0001, HR = 0.4270, 95% CI: 0.2630–0.6930) in patients with BC. Cox univariable and multivariable analyses showed that intravesical therapy, N stage and progression were the independent influence factors of overall survival among bladder cancer patients, CDCA8 expression, tumor grade and progression were the independent influence factors of cancer specific survival among bladder cancer patients. The results of GSEA indicated that CDCA8-regulated gene sets associated with spermatogenesis, G2M checkpoint, E2F targets, Myc targets, mTORC1 signaling, mitotic spindle angiogenesis, PI3K/AKT/mTOR signaling, cholesterol homeostasis and glycolysis. Finally, RT-PCR results confirmed that CDCA8 expression was upregulated in BC ( P =  .0039). CDCA8 is overexpressed in BC and its high levels are correlated with poor clinicopathological features of BC patients. Therefore, CDCA8 may act as a novel prognostic marker and therapeutical target in the diagnosis and treatment of patients with BC.